Development and standardization of a common speech discrimination test for Indians - Maya Devi (Journal of All India Institute of Speech and Hearing)
Speech audiometry has been an important tool in the diagnostic test battery, as it provides a measure of the listener’s response to speech. Discrimination testing clinically aids in the differential diagnosis of conductive, cochlear and retrocochlear pathologies.